Epileptogenic zone detection in MRI negative epilepsy using adaptive thresholding of arterial spin labeling data - Gajdoš, Martin; Říha, Pavel; Kojan, Martin; Doležalová, Irena; Mutsaerts, Henk J M M; Petr, Jan; Rektor, Ivan (Scientific reports, 2021)
Drug-resistant epilepsy is a diagnostic and therapeutic challenge, mainly in patients with negative MRI findings. State-of-the-art imaging methods complement standard epilepsy protocols with new information and help epileptologists to increase the reliability of their decisions. In this study, we investigate whether arterial spin labeling (ASL) perfusion MRI can help localize the epileptogenic zone (EZ). To that end, we developed an image processing method to detect the EZ as an area with hypoperfusion relative to the contralateral unaffected side, using subject-specific thresholding of the asymmetry index in ASL images. We demonstrated three thresholding criteria (termed minimal product criterion, minimal distance criterion, and elbow criterion) on 29 patients with MRI-negative epilepsy (age 32.98 ± 10.4 years). The minimal product criterion showed optimal results in terms of positive predictive value (mean 0.12 in postoperative group and 0.22 in preoperative group) and true positive rate (mean 0.71 in postoperative group and 1.82 in preoperative group). Additionally, we found high accuracy in determining the EZ side (mean 0.86 in postoperative group and 0.73 in preoperative group out of 1.00). ASL can be easily incorporated into the standard presurgical MR protocol, and it provides an additional benefit in EZ localization.
Keywords: spinové značení; Radiographic Image Interpretation, Computer-Assisted; výsledek terapie; Spin Labels; Drug Resistant Epilepsy; Middle Aged; mužské pohlaví; Prospective Studies; Adult; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; rentgenový obraz - interpretace počítačová; Humans; prospektivní studie; lidé středního věku; dospělí; Female; Treatment Outcome; refrakterní epilepsie; lidé; Male